Habitus Belanja Online dan Tren Gaya Hidup Shopaholic di Kalangan Mahasiswa FISIP Universitas Nusa Cendana: Perspektif Cultural Studies - Lasarus Jehamat; Helga M. Evarista Gero; Christine E. Meka (Jurnal Pluralis, 2024)
The growth of internet technology has changed how we shop, with more and more individuals turning to Online shopping. Amid these changes, students have become a significant group in Online shopping trends and Shopaholic behavior. This article aims to investigate the relationship between Online shopping habits and Shopaholic lifestyle trends among students at the Faculty of Social and Political Sciences (FISIP) at Nusa Cendana University, using a Cultural Studies perspective. The research method involves a qualitative approach, with data collection through in-depth interviews and content analysis of narratives of students' Online shopping experiences. The research results show a significant relationship between Online shopping habits and Shopaholic lifestyle trends among Nusa Cendana University FISIP students. Factors such as consumer culture, social identity, and social pressure play an important role in shaping Online shopping patterns and Shopaholic behavior. This analysis provides deep insight into how culture and identity interact with technology to shape consumer behavior among college students. These findings have important implications for further understanding consumer dynamics in the digital era and for developing more effective intervention strategies for managing excessive Online consumption behavior among college students. This study also contributes to the Cultural Studies literature by looking at how culture and identity interact with the Online shopping phenomenon in the context of higher education.